Role of vascular endothelial growth factor in non-small cell lung cancer pathogenesis - Krupnova, E.V.; Shapetska, M.N.; Mikhalenko, E.P.; Chebotaryova, N.V.; Shchayuk, A.N.; Pissarchik, S.N.; Prokhorov, A.V. (Experimental Oncology, 2015)
The angiogenesis is an important process in the pathogenesis of malignancies. It is regulated by various growth factors, with the vascular endothelial growth factor (VEGF) playing the central role. The aim of the present study was to evaluate possible associations of functional VEGF −2578C>A, −634G>C, and +936C>T polymorphisms with the risk for occurrence and progression of non-small cell lung cancer (NSCLC) in patients living in Republic of Belarus. Materials and Methods: A total of 202 patients (147 males and 55 females) diagnosed as having the NSCLC. The control group consisted of 336 individuals (245 males and 91 females) without an oncopathology. The total DNA was isolated from peripheral blood. We investigated the single nucleotide polymorphisms of VEGF (rs 2010963), (rs 699947), (rs 3025039). The genotyping was performed by PCR-RFLP analysis. Results: Our results revealed a marginally significant association of the –2578CC genotype (p=0.002) with a greater degree of tumor spread (Т2–Т4). Heterozygous genotypes –2578СА and +936СT carriers were included into the follow-up group significantly more often (р=0.021 and р=0.012, respectively). Our study demonstrate that VEGF –2578A/C and +936C/T polymorphisms are among the factors determining the individual peculiarities of NSCLC course in this population and can be used for clarifying the prognosis of the disease. Key Words: vascular endothelial growth factor, polymorphism, non-small cell lung cancer.